Compliance with face mask use during the COVID-19 pandemic: a community observational study in Singapore - Sean Wei Xiang Ong; Ying Wei Tang; Kyaw Zaw Linn; Xiao Wei Huan; Allie Lim; Chu Ying Poon; Danielle Hui Ru Tan; Nur Hafizah Binte Hamed; Sharifah Farhanah Binte Syed Husen; Clara Chong Hui Ong; Monica Chan; Shawn Vasoo; et al. (Singapore Medical Journal)
Introduction: Widespread mask use is an important intervention for control of the coronavirus disease 2019 pandemic. However, data on the factors affecting mask use are lacking. In this observational study, we evaluated the proportion of and factors influencing face mask use and related hygiene practices. Methods: We observed randomly selected members from the public in 367 venues across Singapore, and recorded the proportion of individuals with full compliance with mask use and mask hygiene (hand hygiene before and after touching the mask or face). Logistic regression analyses were used to determine variables associated with mask and hand hygiene compliance. Results: We made 3,821 observations — 2,149 (56.2%) females, 3,569 (93.4%) adults (≥21 years), 212 (5.5%) children (6–20 years) and 40 (1.0%) children (2–5 years). The overall full compliance rate (correct mask use), poor compliance rate (incorrect mask use) and absent mask use were 84.5%, 12.9% and 2.6%, respectively. The factors — male gender, fabric mask usage and crowded indoor venues — were associated with lower mask compliance. Face or mask touching behaviour was observed in 10.7% and 13.7% of individuals observed, respectively. Only one individual performed hand hygiene before and after touching the mask. Conclusion: The rate of mask compliance was high, probably due to legislation mandating mask usage. However, specific factors and crowded indoor venues associated with lower mask compliance were identified. We also noted an issue with the absence of hand hygiene before and after face or mask touching. These issues may benefit from targeted public health messaging.